Structure, properties and potential bioactivities of high-purity insoluble fibre from soybean dregs (Okara). (1st December 2021) - Lyu, Bo; Wang, Huan; Swallah, Mohammed Sharif; Fu, Hongling; Shen, Yue; Guo, Zengwang; Tong, Xiaohong; Li, Yang; Yu, Hansong; Jiang, Lianzhou
Graphical abstract: Highlights: High-purity insoluble dietary fibre (HPIDF) can be recovered from Okara. Digestibility of Okara HPIDF was in vitro evaluated. The structure of DF from Okara changes at different digestion stages. Okara HPIDF shows interesting technological and therapeutic properties. Okara HPIDF has potential to be used as a food ingredient. Abstract: High-purity insoluble dietary fibre (HPIDF) was obtained from low-purity dietary fibre (LPDF) of Okara using a combined-enzyme method. For exploring the value of HPIDF as a functional food material, the structure, physicochemical properties, adsorption properties, potential bioactivities of HPIDF and their changes in different stages of digestion were explored in vitro . The results show that HPIDF shows a high perfect oil-holding capacity, higher viscosity, better cation exchange capacity, α-amylase activity ratio due to smaller particle size and larger specific surface area. The heavy metals-adsorption (Cd 2+, Pb 2+, Zn 2+ ) shows the same, especially in simulated gastric fluid, which is similar to the adsorbability of glucose, cholesterol and acrylamide. Beyond the structure, the dissociation degree of some functional groups result from different digestive environments is the possible cause. Okara is an ideal material for the recovery of HPIDF, which has the potential to be processed into functional food materials.